Sosialisasi Pembuatan Media Pembelajaran Interaktif dengan Lectora Inspire di SD Negeri Karang Bagja - Miliyawati, Bety; Budianingsih, Yanry; Gadzali, Silvy Sondari (Jurnal Media Pengabdian Komunikasi, 2024)
Abstract Technology-based interactive learning media is one of the alternatives for teachers in providing learning in the classroom to make it more varied and interesting. The technology is the use of laptops and the lectora inspire application. A teacher must be able to create interesting learning media that is tailored to the needs of students. However, not all teachers are skilled at creating learning media, especially technology-based interactive learning media. Therefore, it is necessary to conduct socialization for teachers, especially at SDN Karang Bagja in creating interactive learning media based on lectora inspire. The purpose of this community service activity is to provide a seminar on the benefits of information technology in education, especially learning in elementary schools, as well as how to create or present interesting learning media using the lectora inspire application to teachers at SDN Karang Bagja. The methods used are in the form of seminars and direct practical assistance to teachers at SDN Karang Bagja. Before this community service activity was carried out, the teachers were given a questionnaire in the form of a google form, based on the results of the questionnaire it was found that the teachers at SDN Karang Bagja had never created interactive learning media based on digital (technology) and did not know or recognize the lectora inspire application. The results of the community service activities in the form of seminars are an increase in participants' knowledge about the benefits of technology in learning and participants understand and can practice making interactive learning media based on Lectora Inspire. Keywords: Media; learning; interaktif; lectora inspire. Abstrak Media pembelajaran interaktif berbasis teknologi merupakan salah satu alternatif guru dalam memberikan pembelajaran di kelas agar lebih bervariatif dan menarik. Teknologi yang dimaksud adalah penggunaan laptop dan aplikasi lectora inspire. Seorang guru harus mampu membuat media pembelajaran yang menarik dan disesuaikan dengan kebutuhan siswa. Namun tidak semua guru terampil membuat media pembelajaran terutama media pembelajaran interaktif berbasis teknologi. Oleh karena itu perlu dilakukan sosialisasi bagi guru-guru khususnya di SDN Karang Bagja dalam pembuatan media pembelajaran interaktif berbasis lectora inspire. Tujuan dari kegiatan pengabdian ini adalah memberikan seminar terkait dengan kebermanfaatan teknologi informasi dalam pendidikan khususnya pembelajaran di sekolah dasar, serta bagaimana langkah pembuatan atau penyajian media pembelajaran yang menarik menggunakan aplikasi lectora inspire kepada para guru di SDN Karang Bagja. Adapun metode yag digunakan adalah berupa seminar dan pendampingan praktik langsung kepada para guru di SDN Karang Bagja. Sebelum dilaksanakan kegiatan pengabdian ini para guru diberikan angket dalam bentuk google form, berdasarkan hasil angket tersebut diketahui bahwa para guru di SDN Karang Bagja belum pernah membuat media pembelajaran interaktif berbasis digital (teknologi) dan belum mengetahui atau mengenal aplikasi lectora inspire. Hasil dari kegiatan pengabdian dalam bentuk seminar ini adalah adanya penambahan pengetahuan peserta tentang kebermanfaatan teknologi dalam pembelajaran serta peserta menjadi paham dan dapat mempraktekkan dalam pembuatan media pembelajaran interaktif berbasis lectora inspire. Kata-kata kunci: Media; pembelajaran; interaktif; lectora inspire.